Uncovering the underlying aspects of successful COVID-19 prevention and control in Thailand through factor analysis: Lessons we have not yet learned from village health volunteers - Kittiporn Nawsuwan; Roshinee Oupra; Noppcha Singweratham; Phayong Thepaksorn (Belitung Nursing Journal, 2023)
Background: The COVID-19 pandemic has posed a global challenge, leading different nations to adopt diverse strategies for prevention and control. In Thailand, Village Health Volunteers (VHVs) have played a pivotal role in the fight against the virus. As the pandemic unfolded, the critical role of VHVs became apparent, prompting a closer examination of their practices and the underlying factors contributing to their effectiveness. Objective: This study aimed to uncover the underlying factors and indicators contributing to the successful prevention and control of COVID-19 by VHVs in Thailand. Methods: The sample group included 10,400 VHVs nationwide. Data were collected from October 2020 to February 2021 using five-point Likert rating scale online questionnaires. Data were analyzed using the Exploratory Factor Analysis technique, with Principal Component Analysis and the orthogonal Varimax method. Results: The study revealed nine effective factors and 52 indicators contributing to the prevention and control of COVID-19 in Thailand. The identified factors are as follows: 1) Personal precautions, 2) Proactive disease control strategy, 3) Awareness of COVID-19 severity, 4) Pride and job motivation, 5) Adequate medical equipment and support, 6) Communication, planning, and monitoring processes, 7) Self-care for health, 8) Data collection, record maintenance, and report submission, and 9) Proper hand washing. Conclusion: This research emphasizes the importance of a holistic approach to community-based health interventions. It highlights the crucial role of VHVs in disseminating information, ensuring preparedness, and fostering a sense of responsibility among community members. This strategic approach will effectively contribute to ongoing efforts to successfully prevent and control the spread of COVID-19 and potential future outbreaks.